Iran’s last sewn boat? In search of the beach-seining āmele along the Persian Gulf coast of Hormozgan Province, Iran - Kalantar, Shadi; Zazzaro, Chiara; Cooper, John P.; Ghidoni, Alessandro (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Recent ethnographic fieldwork along the Persian Gulf coast of southern Iran by the lead author has located probably the last-known sewn vessel in the country – a disused, beach-seining boat known in Bandari as āmele ( عامله ) and Arabic as ʿāmila ( عاملة ) in the village of Bostane, in Hormozgan Province. The research has also yielded new information about this type: its former distribution within Hormozgan is established, its function is elucidated, and aspects of its materials and terminology are documented for the first time. The work builds on previous work by the three co-authors documenting sewn vessels of the same type acquired from Iran by Qatar Museums, Doha, in 2012, and reported at that time as baggāra (Persian بگاره ; Arabic بقّّارة )) on the basis of museum records.